A method for preparing a degradable hemostatic gel dressing

By introducing trialdehyde polyester-based quaternary ammonium salts as crosslinking agents into chitosan and sodium alginate gel dressings to form a three-dimensional crosslinking network, the shortcomings of existing gel dressings in hemostatic, antibacterial and degradable properties are solved, and higher tensile strength, water absorption and antibacterial properties are achieved.

CN119055823BActive Publication Date: 2025-04-08ZHEJIANG AOQI MEDICAL DRESSING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411168143.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2025-04-08
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Existing chitosan and sodium alginate gel dressings perform poorly in hemostatic and antibacterial properties, while also having low degradability.

Method used

Trialdehyde polyester-based quaternary ammonium salt is used as a crosslinking agent to form a three-dimensional crosslinking network by crosslinking reaction with the amino and hydroxyl groups of chitosan and sodium alginate, which improves the tensile strength and water absorption of the gel dressing, and enhances the antibacterial properties through the quaternary ammonium salt groups.

Benefits of technology

It significantly improves the degradability of gel dressings, enhances its antibacterial properties and hemostatic effect, while improving tensile strength and water absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005008420590000041
    Figure BDA0005008420590000041
  • Figure BDA0005008420590000042
    Figure BDA0005008420590000042
  • Figure BDA0005008420590000043
    Figure BDA0005008420590000043
Patent Text Reader

Abstract

The present invention relates to the field of biomedical technology, and discloses a preparation method of a degradable hemostatic gel dressing. The present invention uses citric acid, p-chloromethylbenzoyl chloride, 5-hydroxyvaleraldehyde, and alkyl dimethyl tertiary amine as reactants, and obtains trialdehyde polyester quaternary ammonium salt through esterification and quaternization reaction. Green, environmentally friendly and nontoxic biomass degradable chitosan and sodium alginate are used as the base material of the gel dressing, and trialdehyde polyester quaternary ammonium salt is used as a cross-linking agent to improve the tensile strength, water absorption rate and liquid absorption performance of the gel dressing, and the hemostatic performance of the gel dressing can be improved. The trialdehyde polyester quaternary ammonium salt contains a quaternary ammonium salt antibacterial group, which can enhance the antibacterial performance of the gel dressing, and contains a plurality of hydrolyzable ester groups. After the gel dressing is soaked in water, the ester group is hydrolyzed and broken, so that the gel dressing shows a higher hydrolysis weight loss rate and degradable performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedicine, and in particular to a method for preparing a degradable hemostatic gel dressing. Background Art

[0002] Chitosan, sodium alginate, etc. are natural polysaccharide derivatives, cheap, easy to obtain, green, environmentally friendly, non-toxic and pollution-free. Chitosan has certain antibacterial properties and is widely used in gel materials, gauze, dressings and other medical supplies. Introducing antibacterial groups such as quaternary ammonium salts into chitosan can further improve the antibacterial properties of chitosan.

[0003] At present, with glyoxal, glutaraldehyde etc., epichlorohydrin etc. as cross-linking agent, chitosan, sodium alginate are carried out cross-linking reaction, can obtain materials such as gel, composite membrane with excellent performance.But the materials such as gel and composite membrane obtained can only be biodegraded usually, do not have hydrolysis, and degradable performance is lower.The patent disclosure of announcement number CN114887108B is a kind of preparation method of sodium alginate / chitosan quaternary ammonium salt double cross-linked medical dressing with gradient pore structure, with sodium alginate, chitosan quaternary ammonium salt, chloride, calcium carbonate etc. as raw materials, the sodium alginate / chitosan quaternary ammonium salt double cross-linked medical dressing obtained has excellent antibacterial, hemostasis, liquid absorption and biocompatibility.But this medical dressing does not show good mechanical strength and hydrolysis degradation performance. Summary of the invention

[0004] The invention solves the problem that chitosan and sodium alginate gel dressings have poor hemostatic and antibacterial properties, and at the same time significantly improves the degradability of the gel dressing.

[0005] The technical scheme provided by the present invention is: a preparation method of a degradable hemostatic gel dressing: adding acetic acid solution and 100 parts by weight of chitosan into a flask, stirring and dissolving, adding 30-150 parts by weight of sodium alginate, stirring and adding 4-20 parts by weight of trialdehyde polyester quaternary ammonium salt, stirring and reacting, filtering, washing with ethanol, soaking the product in distilled water for 3 days, changing the water every 12 hours, and drying to obtain a degradable hemostatic gel dressing.

[0006] The trialdehyde polyester quaternary ammonium salt has the following structural formula (I):

[0007] n is 14, 15, 16, 17 or 18.

[0008] Preferably, the mass fraction of the acetic acid solution is 2-2.5%.

[0009] Preferably, the reaction temperature is 40-60° C., and the reaction time is 4-10 h.

[0010] Preferably, the preparation method of trialdehyde polyester quaternary ammonium salt is:

[0011] Step (1), add acetone, triethylamine, citric acid, and p-chloromethylbenzoyl chloride in a molar ratio of (1-1.1):(1.1-1.3):1 into a flask, stir and react at room temperature for 3-6 hours, evaporate under reduced pressure, wash with saturated sodium chloride solution, and dry to obtain intermediate A.

[0012] Step (2), add toluene, intermediate A, p-toluenesulfonic acid, and 5-hydroxyvaleraldehyde in a molar ratio of 1:(0.08-0.12):(3.3-4.2) into a flask, raise the temperature to 80-90°C, stir and react for 24-36 hours, distill under reduced pressure, and recrystallize the product in ethyl acetate to obtain intermediate B.

[0013] Step (3), acetonitrile, intermediate B, and alkyl dimethyl tertiary amine in a molar ratio of 1: (1-1.4) are added to a flask, wherein the alkyl dimethyl tertiary amine has the structural formula n is 14, 15, 16, 17 or 18; the temperature is raised to 80-85°C, stirred and condensed under reflux for 12-18 hours, distilled under reduced pressure, washed with petroleum ether, and the product was recrystallized in ethanol to obtain a trialdehyde polyester quaternary ammonium salt.

[0014] The technical effect of the invention is that: the invention uses citric acid, p-chloromethylbenzoyl chloride, 5-hydroxyvaleraldehyde and alkyl dimethyl tertiary amine as reactants, and obtains trialdehyde polyester quaternary ammonium salt through esterification reaction and quaternization reaction.

[0015] The present invention uses green, environmentally friendly, non-toxic biodegradable chitosan and sodium alginate as the base material of the gel dressing, and uses trialdehyde polyester quaternary ammonium salt as a cross-linking agent, which contains multiple aldehyde groups, can react with amino groups, hydroxyl groups and other groups of chitosan and sodium alginate to form a three-dimensional cross-linked network, and multiple aldehyde groups are conducive to improving the cross-linking degree between chitosan and sodium alginate, thereby improving the tensile strength of the gel dressing. And the three-dimensional cross-linked network has a certain pore structure, which is conducive to improving the water absorption rate of the gel dressing. The higher the water absorption rate, the better the liquid absorption, and the hemostatic performance of the gel dressing can be improved.

[0016] The trialdehyde multiester quaternary ammonium salt of the present invention contains a quaternary ammonium salt antibacterial group, which can enhance the antibacterial performance of the gel dressing and show a larger diameter of the inhibition zone. In addition, the trialdehyde multiester quaternary ammonium salt contains a plurality of hydrolyzable ester groups. After the gel dressing is soaked in water, the ester groups are hydrolyzed and broken, and the chitosan and sodium alginate cannot be chemically cross-linked, so that the water-soluble chitosan and sodium alginate are dissolved, thereby making the gel dressing show a higher hydrolysis weight loss rate and degradable performance. DETAILED DESCRIPTION

[0017] In order to further understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1

[0019] Step (1), add 70mL acetone, 30mmol triethylamine, 33mmol citric acid, 30mmol p-chloromethylbenzoyl chloride into a flask, stir and react at room temperature for 6h, distill under reduced pressure, wash with saturated sodium chloride solution, and dry to obtain intermediate A. The reaction formula is as follows:

[0020]

[0021] Step (2), add 80 mL of toluene, 20 mmol of intermediate A, 2.4 mmol of p-toluenesulfonic acid, and 66 mmol of 5-hydroxyvaleraldehyde to a flask, heat to 80° C., stir and react for 24 hours, distill under reduced pressure, and recrystallize the product in ethyl acetate to obtain intermediate B. The reaction formula is as follows:

[0022]

[0023] Step (3), add 250mL acetonitrile, 30mmol intermediate B, 39mmol octadecyldimethyl tertiary amine to a flask, heat to 80°C, stir and condense under reflux for 18h, distill under reduced pressure, wash with petroleum ether, and recrystallize the product in ethanol to obtain trialdehyde polyester quaternary ammonium salt. The reaction formula is as follows:

[0024]

[0025] Step (4), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 2g of trialdehyde polyester quaternary ammonium salt, heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0026] Example 2

[0027] Step (1), add 80 mL of acetone, 33 mmol of triethylamine, 39 mmol of citric acid, and 30 mmol of p-chloromethylbenzoyl chloride into a flask, stir and react at room temperature for 3 h, evaporate under reduced pressure, wash with saturated sodium chloride solution, and dry to obtain intermediate A.

[0028] Step (2), add 80 mL of toluene, 20 mmol of intermediate A, 1.6 mmol of p-toluenesulfonic acid, and 84 mmol of 5-hydroxypentanal into a flask, heat to 90° C., stir and react for 24 h, distill under reduced pressure, and recrystallize the product from ethyl acetate to obtain intermediate B.

[0029] Step (3), add 250mL acetonitrile, 30mmol intermediate B, and 30mmol hexadecyldimethyl tertiary amine into a flask, heat to 85°C, stir and condense under reflux for 12h, distill under reduced pressure, wash with petroleum ether, and recrystallize the product in ethanol to obtain a trialdehyde polyester quaternary ammonium salt.

[0030] Step (4), add 4L of 2.5% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 45g of sodium alginate, stir to add 2g of trialdehyde polyester quaternary ammonium salt, heat to 60°C, stir to react for 4h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0031] Example 3

[0032] Step (1), add 60 mL of acetone, 30 mmol of triethylamine, 33 mmol of citric acid, and 30 mmol of p-chloromethylbenzoyl chloride into a flask, stir and react at room temperature for 5 h, evaporate under reduced pressure, wash with saturated sodium chloride solution, and dry to obtain intermediate A.

[0033] Step (2), add 100 mL of toluene, 20 mmol of intermediate A, 2 mmol of p-toluenesulfonic acid, and 72 mmol of 5-hydroxypentanal into a flask, raise the temperature to 80° C., stir and react for 36 h, distill under reduced pressure, and recrystallize the product in ethyl acetate to obtain intermediate B.

[0034] Step (3), add 250mL acetonitrile, 30mmol intermediate B, 42mmol tetradecyldimethyl tertiary amine into a flask, heat to 80°C, stir and condense under reflux for 18h, distill under reduced pressure, wash with petroleum ether, and recrystallize the product from ethanol to obtain trialdehyde polyester quaternary ammonium salt.

[0035] Step (4), add 4L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 75g of sodium alginate, stir to add 2g of trialdehyde polyester quaternary ammonium salt, heat to 40°C, stir to react for 10h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0036] Comparative Example 1

[0037] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, then add 15g of sodium alginate, heat to 40°C, stir for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0038] Comparative Example 2

[0039] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 10mL of an aqueous solution containing 2g of glutaraldehyde, heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0040] Comparative Example 3

[0041] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir and dissolve, then add 15g of sodium alginate, stir and add 2g of intermediate B (the same preparation method as in Example 1), heat to 40°C, stir and react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0042] Soak the degradable hemostatic gel dressing in distilled water for 12 hours, take out the gel dressing, absorb the water on the surface of the membrane with filter paper, weigh it, and calculate the water absorption rate. Water absorption rate = (m1-m0) / m0×100%; m1 is the mass of the gel dressing after absorbing water, and m0 is the mass of the gel dressing after absorbing water. The higher the water absorption rate, the better the liquid absorption.

[0043] The tensile strength of the gel dressing was tested using a universal testing machine, with a tensile rate of 100 mm / min and a sample size of 100 mm × 40 mm × 4 mm. The test results are shown in the table below.

[0044] Water absorption (%) Tensile strength(MPa) Example 1 1365.7 15.5 Example 2 1665.0 17.2 Example 3 1803.5 13.4 Comparative Example 1 965.8 10.3 Comparative Example 2 1123.6 15.9

[0045] As can be seen from the above table, the chitosan and sodium alginate of Examples 1, 2, and 3 are added with trialdehyde polyester quaternary ammonium salt, which contains multiple aldehyde groups, and can react with amino groups, hydroxyl groups, and other groups of chitosan and sodium alginate to form a three-dimensional cross-linked network. Multiple aldehyde groups are beneficial to improve the degree of cross-linking between chitosan and sodium alginate, thereby improving the tensile strength of the gel dressing. And the three-dimensional cross-linked network has a certain pore structure, which is beneficial to improve the water absorption rate of the gel dressing. The higher the water absorption rate, the better the liquid absorption, which can improve the hemostatic performance of the gel dressing.

[0046] Compared with Example 1, Comparative Example 1 uses common glutaraldehyde as a crosslinking agent to crosslink chitosan and sodium alginate, and its water absorption rate and tensile strength are significantly higher than those of Comparative Example 1, but lower than those of Example 1, which may be because glutaraldehyde contains only two aldehyde groups, and the degree of crosslinking between chitosan and sodium alginate is lower than that of trialdehyde polyester quaternary ammonium salt containing three aldehyde groups, and trialdehyde polyester quaternary ammonium salt contains hydrophilic quaternary ammonium salt groups, which can improve the hydrophilicity and water absorption rate of the gel dressing. As a result, the water absorption rate and tensile strength of Comparative Example 2 are lower than those of Example 1.

[0047] In Comparative Example 2, intermediate B is used as a cross-linking agent to cross-link chitosan and sodium alginate. The gel dressing also has good water absorption and tensile strength, but the water absorption is slightly lower than that of Example 1. This may be because intermediate B does not contain a hydrophilic quaternary ammonium salt group, resulting in the hydrophilicity and water absorption of the gel dressing being lower than those of Example 1.

[0048] Escherichia coli and Staphylococcus aureus were used as test bacteria. 0.5 mL of activated test bacteria suspension (10 8 cfu / mL) was evenly coated on the surface of the agar culture medium, and the gel dressing film sterilized by ultraviolet light was attached to the surface of the culture medium, and placed in a constant temperature incubator. The culture temperature was set to 37°C and the time was set to 48h. After culture, the diameter of the inhibition zone was measured.

[0049] The gel dressings were immersed in PBS buffer solution at room temperature for 10-30 days, filtered, dried, weighed, and the weight loss rate R was calculated. R = (M0-M1) / M0×100%. M0 is the initial mass of the gel dressing before immersion. M1 is the mass of the gel dressing after immersion.

[0050]

[0051] As can be seen from the above table, trialdehyde multi-ester quaternary ammonium salts are added to the chitosan and sodium alginate of Examples 1, 2, and 3, which contain quaternary ammonium salt antibacterial groups, thereby enhancing the antibacterial properties of the gel dressing and having a larger inhibition zone diameter. And after being soaked in water for 10-30 days, the gel dressing loses weight significantly, because trialdehyde multi-ester quaternary ammonium salts contain multiple hydrolyzable ester groups, and after the gel dressing is soaked in the water medium, the ester groups are hydrolyzed and broken, and the chitosan and sodium alginate cannot be chemically cross-linked, so that the water-soluble chitosan and sodium alginate are dissolved, so that the gel dressing shows a higher weight loss rate and degradable performance.

[0052] In Comparative Example 1, glutaraldehyde is used as a cross-linking agent, which does not contain a hydrolyzable ester group. After being immersed in water, the gel dressing cannot be hydrolyzed and almost does not lose weight.

[0053] In Comparative Example 2, intermediate B is used as a cross-linking agent, which also contains multiple hydrolyzable ester groups. After the gel dressing is soaked in water, the ester groups are hydrolyzed and broken, so that the water-soluble chitosan and sodium alginate are dissolved, so that the gel dressing exhibits a higher weight loss rate and degradable performance.

[0054] Example 4

[0055] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 4g of trialdehyde polyester quaternary ammonium salt (the same preparation method as in Example 1), heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0056] Example 5

[0057] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 6g of trialdehyde polyester quaternary ammonium salt (the same preparation method as in Example 1), heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0058] Example 6

[0059] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 8g of trialdehyde polyester quaternary ammonium salt (the same preparation method as in Example 1), heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0060] Example 7

[0061] Step (1), add 3L of 2% acetic acid solution and 50g of chitosan into a flask, stir to dissolve, add 15g of sodium alginate, stir to add 10g of trialdehyde polyester quaternary ammonium salt (the same preparation method as in Example 1), heat to 40°C, stir to react for 6h, filter, wash with ethanol, soak and wash the product in distilled water for 3 days, change the water every 12h, and dry to obtain a degradable hemostatic gel dressing.

[0062] The performance of the degradable hemostatic gel dressing was tested according to the above method. The test structure is shown in the table below.

[0063]

[0064]

[0065] As can be seen from the above table, at different dosages of trialdehyde polyester quaternary ammonium salt, the degradable hemostatic gel dressing showed good water absorption and tensile strength. It also had a large diameter of the inhibition zone and strong antibacterial properties, a high hydrolysis weight loss rate, and good degradability.

[0066] The present invention provides a chitosan / quaternized chitosan sponge and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a degradable hemostatic gel dressing, characterized in that: The preparation method is as follows: add acetic acid solution and 100 parts by weight of chitosan into a flask, stir and dissolve, then add 30-150 parts by weight of sodium alginate, stir and add 4-20 parts by weight of trialdehyde polyester quaternary ammonium salt, stir and react, filter, wash with ethanol, soak the product in distilled water for 3 days, change the water every 12 hours, and dry to obtain a degradable hemostatic gel dressing; The trialdehyde polyester quaternary ammonium salt has the structural formula (I) as follows: n is 14, 15, 16, 17 or 18.

2. The method for preparing the degradable hemostatic gel dressing according to claim 1, characterized in that: The mass fraction of the acetic acid solution is 2-2.5%.

3. The method for preparing the degradable hemostatic gel dressing according to claim 1, characterized in that: The reaction temperature is 40-60°C, and the reaction time is 4-10h.

4. The method for preparing the degradable hemostatic gel dressing according to claim 1, characterized in that: The preparation method of the trialdehyde polyester quaternary ammonium salt is: Step (1), add acetone, triethylamine, citric acid, and p-chloromethylbenzoyl chloride into a flask, stir and react at room temperature for 3-6 hours, distill under reduced pressure, wash, and dry to obtain intermediate A; Step (2), adding toluene, intermediate A, p-toluenesulfonic acid, and 5-hydroxyvaleraldehyde into a flask, stirring for reaction, distilling under reduced pressure, and recrystallizing to obtain intermediate B; Step (3), add acetonitrile, intermediate B, and alkyl dimethyl tertiary amine into a flask, stir to react, distill under reduced pressure, wash, and recrystallize to obtain a trialdehyde polyester quaternary ammonium salt.

5. The method for preparing the degradable hemostatic gel dressing according to claim 4, characterized in that: In the step (1), the molar ratio of triethylamine, citric acid and p-chloromethylbenzoyl chloride is (1-1.1):(1.1-1.3):

1.

6. The method for preparing the degradable hemostatic gel dressing according to claim 4, characterized in that: In the step (2), the molar ratio of intermediate A, p-toluenesulfonic acid, and 5-hydroxyvaleraldehyde is 1:(0.08-0.12):(3.3-4.2).

7. The method for preparing the degradable hemostatic gel dressing according to claim 4, characterized in that: In the step (2), the reaction temperature is 80-90°C and the reaction time is 24-36h.

8. The method for preparing the degradable hemostatic gel dressing according to claim 4, characterized in that: In the step (3), the molar ratio of intermediate B to alkyl dimethyl tertiary amine is 1:(1-1.4); the structural formula of alkyl dimethyl tertiary amine is n is 14, 15, 16, 17 or 18.

9. The method for preparing the degradable hemostatic gel dressing according to claim 4, characterized in that: In the step (3), the reaction temperature is 80-85°C and the reaction time is 12-18h.

Citation Information

Patent Citations

  • A method for preparing a sodium alginate / chitosan quaternary ammonium salt double crosslinked medical dressing with a gradient pore structure

    CN114887108B

  • Medical composite hemostatic sponge for vacuum drainage and preparation method thereof

    CN108066811A

  • Preparation method of sodium alginate / chitosan quaternary ammonium salt bi-crosslinking medical dressing with gradient pore structure

    CN114887108A